Experimental Zika virus infection of Jamaican fruit bats (Artibeus jamaicensis) and possible entry of virus into brain via activated microglial cells. - Ashley Malmlov; Collin Bantle; Tawfik Aboellail; Kaitlyn Wagner; Corey L Campbell; Miles Eckley; Nunya Chotiwan; Rebekah C Gullberg; Rushika Perera; Ronald Tjalkens; Tony Schountz (Public Library of Science (PLoS), 2019)
The emergence of Zika virus (ZIKV) in the New World has led to more than 200,000 human infections. Perinatal infection can cause severe neurological complications, including fetal and neonatal microcephaly, and in adults there is an association with Guillain-Barré syndrome (GBS). ZIKV is transmitted to humans by Aedes sp. mosquitoes, yet little is known about its enzootic cycle in which transmission is thought to occur between arboreal Aedes sp. mosquitos and non-human primates. In the 1950s and '60s, several bat species were shown to be naturally and experimentally susceptible to ZIKV with acute viremia and seroconversion, and some developed neurological disease with viral antigen detected in the brain. Because of ZIKV emergence in the Americas, we sought to determine susceptibility of Jamaican fruit bats (Artibeus jamaicensis), one of the most common bats in the New World. Bats were inoculated with ZIKV PRVABC59 but did not show signs of disease. Bats held to 28 days post-inoculation (PI) had detectable antibody by ELISA and viral RNA was detected by qRT-PCR in the brain, saliva and urine in some of the bats. Immunoreactivity using polyclonal anti-ZIKV antibody was detected in testes, brain, lung and salivary glands plus scrotal skin. Tropism for mononuclear cells, including macrophages/microglia and fibroblasts, was seen in the aforementioned organs in addition to testicular Leydig cells. The virus likely localized to the brain via infection of Iba1+ macrophage/microglial cells. Jamaican fruit bats, therefore, may be a useful animal model for the study of ZIKV infection. This work also raises the possibility that bats may have a role in Zika virus ecology in endemic regions, and that ZIKV may pose a wildlife disease threat to bat populations.